SARA READING COMPONENTS TESTS, RISE FORM: TEST DESIGN AND TECHNICAL ADEQUACY. Issue 1 (8th August 2014) - Sabatini, John; Bruce, Kelly; Steinberg, Jonathan
ABSTRACT: This paper describes the design, development, and technical adequacy of the Reading Inventory and Student Evaluation (RISE) form of the Study Aid and Reading Assessment (SARA) reading components computer‐delivered assessment. The RISE form, designed for middle‐school students, began through a joint project between the Strategic Education Research Partnership (SERP), ETS, and a large urban school district, where middle‐school literacy had been identified as an area needing improvement. Educators were interested in understanding more about the component skills of their middle‐school students, particularly their struggling readers, using an efficient and reliable assessment. To date, results from our piloting of the RISE form with middle‐school students have established its technical adequacy. In the future, we plan to expand the RISE to create parallel forms for 6th‐to‐8th graders as well as to explore development of new test forms at other points in the grade continuum.